If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 17 = 2x + 287 Reorder the terms: 17 + 11x = 2x + 287 Reorder the terms: 17 + 11x = 287 + 2x Solving 17 + 11x = 287 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 17 + 11x + -2x = 287 + 2x + -2x Combine like terms: 11x + -2x = 9x 17 + 9x = 287 + 2x + -2x Combine like terms: 2x + -2x = 0 17 + 9x = 287 + 0 17 + 9x = 287 Add '-17' to each side of the equation. 17 + -17 + 9x = 287 + -17 Combine like terms: 17 + -17 = 0 0 + 9x = 287 + -17 9x = 287 + -17 Combine like terms: 287 + -17 = 270 9x = 270 Divide each side by '9'. x = 30 Simplifying x = 30
| 4w^2+2=-9w | | 1+-2gk=h | | 12x+26=6x+206 | | 38-4x-3.147x=0 | | 18-7x=94 | | 25x^2+9=20 | | 72x-9/2x^2=0 | | 5(3y+4)=14y | | 100x^2+120x+36=0 | | 5(3y-4)=14y | | 7-(x/8)=(x/6) | | 4u^2-11u+6= | | (3c-4)= | | 3x+7=-32 | | 3x^2-2x-21= | | (7y-2)/3=-4/(y-3) | | 10/2p-6/20=15/20p+9/20 | | Ax-1=bx | | 18-4200/x^2 | | (3x^2+2x-9)-(6x^2-8)= | | 25200/24 | | 7-2800/x^2=0 | | 8/32= | | log(9)7+log(9)4= | | 5x-9=x+6 | | x^2+7x-6=9x-6 | | (3x^7-3x^4+8x)+(6x^7-5x^4+7x)= | | 10=5/2v | | 5=8/x+2 | | x^2-2x-7=1 | | X+20x-8=0 | | 2w/7=6 |